Distribution of Cylindrospermopsis raciborskii (Cyanobacteria) in Sri Lanka - S. K. Yatigammana (Ceylon Journal of Science, 2017)
Sri Lanka is a tropical continental island which consists of 103 natural rivers and over ten thousand man-made lakes.  Majority of these water resources are known to be contaminated with different types of toxigenic cyanobacteria making water unsuitable for human and animal consumption. Cylindrospermopsis raciborskii, a toxin producing tropical cyanobacterium, recently recorded at high abundances in lentic waters of the country. This species is highly adaptive and exhibit different morphotypes: straight, coiled and sigmoid- shaped trichomes under different environmental conditions. Distribution and abundance of the species is mainly depending on the environmental factors and therefore remedies can be proposed to keep the populations under control. This preliminary study was conducted to understand the prevalence of C. raciborskii, in Sri Lankan reservoirs. Sixty three reservoirs representing all climatic regions with varying environmental conditions were assessed using standard procedures. The results of the study reviewed that C. raciborskii is a dominant cyanobacterium species especially during the dry season in shallow urban reservoirs, terminal reservoirs in large cascades, reservoirs with low flushing rates and deep reservoirs with persistent water stratification. Morphological variations were common in urban and shallow reservoirs that maintain high water retention time. They commonly occur in coiled–shape. However, in eutrophic water bodies they are appeared to support other morphotypes: straight, sigmoid or tricomatous. Further, it was noticed that the cell size of C. raciborskii is exceptionally large (width 3.5 µm and length 7µm) in a high altitudinal wet–zone reservoir that usually maintains temperature range of 10oC - 20oC throughout the year. The results showed that C. raciborskii is widely distributed all over the country and the presence of several morphotypes signifies its potential for rapid distribution.